Stainless steel channel sections under combined compression and minor axis bending – part 1 : experimental study and numerical modelling - Liang, Yating (2020)
The local cross-section behaviour of stainless steel channel sections under the combined actions of axial compression and minor axis bending moment is investigated in the present paper and its companion paper, based on a comprehensive experimental and numerical study. Two channel section sizes were considered in the experimental programme, with the test specimens laser-welded at the two flange-to-web junctions from hot-rolled EN 1.4307 and EN 1.4404 austenitic stainless steel plates. The experiments involved initial local geometric imperfection measurements and 15 eccentrically loaded stub column (combined loading) tests. The loading eccentricity was varied to achieve a range of ratios of axial compression to minor axis bending moment; both orientations of bending (web in compression and web in tension) were considered. The test setup and procedures, together with the key experimental observations, including the load-carrying and deformation capacities, load-end rotation histories and failure modes, are fully reported. A finite element simulation study is then presented, in which the models were first validated against the obtained test results and then employed, in the companion paper, for parametric investigations and the assessment of design provisions.